New Theoretical Trends in Food Geography and the Perspective on Japan - IKEDA, Masashi; IWAMA, Nobuyuki; IGA, Masaya; IKEGUCHI, Akiko; TAKAHASHI, Makoto; GOTO, Takuya; ARAKI, Hitoshi; TATEMI, Junya (E-journal GEO, 2007)
Japanese society has recently seen growing public concern about the issues of food. The government increasingly takes responsibility for food security in the globalized food systems, while new types of food practice are certainly emerging in farms, markets, restaurants and household. How can we understand such complicated situations? The food geography, tackling these issues especially in the western developed countries, probably provides a significant arena for the inter- and intra-disciplinary discussion. In order to attend this arena, as well as to understand the current situation of food production and consumption in Japan itself, it is necessary to share the key concepts and frameworks, which have dominated some recent subjects of food geography. This paper presents some discussion about how we can approach the issues of food in particular in the political-economic and socio-cultural contexts of Japan, conceptually focusing on the notions of the food regime, the global commodity chain, food deserts, the food network, the economics of conventions and actor-network theory, respectively. Most if not all of these notions have been articulated in the contexts of Anglo-American and European countries. This paper attempts to explore the possibilities of applying them to the Japanese context, with reference both to the academic background of their proponents and to the contextual difference between western and Japanese societies. As concluding remarks, we argue that we need further international and inter-disciplinary discussions and empirical studies from cross-cultural perspectives.